Perancangan Sistem Administrasi Holding Berbasis Website Pada Sabana Group - Zainah, Hana; Sitorus, Anwar Tonggo; Rinaldo, Rinaldo; Juwari, Juwari; Samroh, Samroh (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This research aims to design a web-based holding administration system at Sabana Group to address administrative problems that are still handled manually and semi-manually. The existing administrative process has the potential to cause data duplication, document loss, slow data retrieval, and low efficiency and accuracy in information management. The system development method used in this study is the prototype method, with data collection techniques including observation, interviews, and literature studies. The system design utilizes Unified Modeling Language (UML), while the implementation is carried out using a website-based platform with PHP, MySQL, and XAMPP as the local server. System testing is conducted using blackbox testing to ensure that system functionalities meet user requirements. The results indicate that the web-based holding administration system improves the effectiveness and efficiency of administrative processes, reduces recording errors and duplicate data, accelerates historical data retrieval, and supports integrated and real-time administrative monitoring. This system is expected to serve as a structured, accurate, and sustainable administrative management solution for Sabana Group.